Efektivitas Modul Pendidikan Agama Kristen untuk Nilai Integritas dan Anti-Korupsi pada Siswa Sekolah Menengah Atas - Oscard J.S. May; Vini Irviana Hiara; Sania Dilago; Jerizal Petrus (Jurnal Ilmiah Religiosity Entity Humanity (JIREH), 2026)
Christian Religious Education (CRE) plays a strategic role in shaping students' character and morals, particularly in instilling values of integrity and anti-corruption. This study aims to evaluate the effectiveness of a specially designed CRE module to internalize these values among high school (SMA) students. The research method employed is a quasi-experimental design with pretest-posttest on class XI students of SMK Percis Halmahera. The results indicate that the specifically designed CRE module is effective in improving students' understanding and awareness of the importance of integrity and anti-corruption. Additionally, the module successfully fosters positive attitudes among students towards honest and responsible living practices. These findings suggest that CRE can be an effective means of shaping students' characters with integrity and anti-corruption values.